Influence of Radiation and Convection on 3D-Casson Hybrid Nanofluid Flow in the Presence of Suction Over a Rotary Sheet - Prathiba, Alfunsa (Communications in Mathematics and Applications, 2022)
The current research looks at how the radiation affects the convective hybrid Casson 3D flow in the presence of suction. The fluid analysed was a hybrid nanofluid made up of Alumina (Al2O3) and Copper (Cu) nanoparticles diffused in base fluid (Water). After simplification, the flow control equations were programmed and solved employing the MATLAB software and the bvp4c code. Figures depict the study’s most important findings, such as the impact of several physical elements such as convection, radiation, and suction on the velocity profile, mass transfer, temperature field, friction factor, and heat transfer coefficient. According to the key findings, the Casson Hybrid nanofluid has a better property than normal fluids. It can also be deduced that as the scale of the radiation constraint strengthens, the temperature field improves. Tables were used to validate our findings with cited papers.
Keywords: Richardson number; Radiation; Suction; Hybrid Casson Fluid; Rotating sheet; Heat source